Treatment of children with frequently relapsing steroid-sensitive nephrotic syndrome: recent trial results. (November 2014) - Benz, Marcus R; Toenshoff, Burkhard; Weber, Lutz T
Despite being an orphan disease idiopathic nephrotic syndrome in children is the most frequent glomerular disease in this age group. A total of 80–90% of children between 2 and 10 years of age respond to corticosteroids, but carry the risk of relapses that may even appear frequently (frequently relapsing nephrotic syndrome, [FRNS]). To avoid repeated courses of corticosteroids and associated drug toxicity in these patients manifold strategies for a corticosteroid-sparing treatment of FRNS exist, but evidence on their efficacy and safety is low. This article discusses the results of recent therapeutic trials on FRNS and their possible impact on existing guidelines. Since the prognosis of steroid-sensitive nephrotic syndrome toward renal function is generally good, not only the efficacy but also the toxicity of different treatment regimens is discussed.